Effects of the endothelin A receptor antagonist darusentan on blood pressure and vascular contractility in type 2 diabetic Goto-Kakizaki rats - Witte, Klaus; Reitenbach, Ina; Stolpe, Kerstin; Schilling, Lothar; Kirchengast, Michael; Lemmer, Björn (Journal of cardiovascular pharmacology, 2003)
The present study evaluated the effects of long-term treatment with the endothelin A (ETA) receptor antagonist darusentan (LU135252) on blood pressure (BP) and vascular target-organ damage in spontaneously type 2 diabetic Goto-Kakizaki (GK) rats. BP was monitored by radiotelemetry in untreated and darusentan-treated GK rats from 10-24 weeks of age. Relaxation of mesenteric artery segments by acetylcholine (ACh) and sodium nitroprusside (SNP) was measured to assess endothelium-dependent and -independent vasorelaxation. Aortic soluble guanylyl cyclase (sGC) activity was studied in vitro after stimulation by the nitric oxide (NO) donor diethylamine-NONOate. Untreated GKs were mildly hypertensive and showed a blunted vascular relaxation by ACh and SNP and a reduction in NO-stimulated sGC activity in comparison with Wistar control rats. Darusentan led to a small but sustained reduction in 24-h BP but did not restore the endothelium-dependent vasorelaxation nor the NO-stimulated cGMP formation in GK rats. The present findings suggest that an activated endothelin pathway may contribute to elevated BP but is not involved in vascular dysfunction in this animal model of type II diabetes.